If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 8 = 9m + -4 Reorder the terms: 8 + 5m = 9m + -4 Reorder the terms: 8 + 5m = -4 + 9m Solving 8 + 5m = -4 + 9m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9m' to each side of the equation. 8 + 5m + -9m = -4 + 9m + -9m Combine like terms: 5m + -9m = -4m 8 + -4m = -4 + 9m + -9m Combine like terms: 9m + -9m = 0 8 + -4m = -4 + 0 8 + -4m = -4 Add '-8' to each side of the equation. 8 + -8 + -4m = -4 + -8 Combine like terms: 8 + -8 = 0 0 + -4m = -4 + -8 -4m = -4 + -8 Combine like terms: -4 + -8 = -12 -4m = -12 Divide each side by '-4'. m = 3 Simplifying m = 3
| 15k^2+6k= | | -14-n=-7 | | 2a-7=-7 | | x^2-8xy-9y^2= | | a^2-4ac+ab-4bc= | | 720=(2x-6)(x+6) | | (sin(5x))/x | | -40=r-19 | | 27-b=16 | | 27x-8.5x+27x-4.6=3-.5 | | 3x^2+15= | | 16=4n-18 | | (3x^3+4x-1)(x^2+1)= | | 24a^2b^2-18ab= | | -2+1/3a=-9 | | -2u-3=11 | | y^3-2y^2=0 | | 2x^3-5x+1= | | 2-5x+3=5-2x+7-10x | | 4x+9=-7x+31 | | 7x+11=3x+59 | | 3-a=4a+13 | | -5x+6x+15-12x= | | -4.4s=-5.5s-4.3 | | 2+(-21)= | | -3x+25+x+21=3 | | -23-3y+31= | | 15x-7=14x+12 | | T-7=30 | | -3y-1=-2y-8 | | 3y-23-6y+31= | | Y+5=-1 |